Over-Expression of Pancreatic Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Aggravates Cerulein-Induced Acute Pancreatitis in Mice - Ken-ichi Hamagami; Yusuke Sakurai; Norihito Shintani; Naoko Higuchi; Kazuya Ikeda; Hitoshi Hashimoto; Akinobu Suzuki; Hiroshi Kiyama; Akemichi Baba (Elsevier, 2009)
Abstract.: Development of human chronic pancreatitis is associated with intrapancreatic accumulation of pituitary adenylate cyclase-activating polypeptide (PACAP) accompanied with an altered inflammatory response (Michalski et al., Am J Physiol Gastrointest Liver Physiol. 2008;294:G50-G57). To investigate the role of pancreatic PACAP in the development of acute pancreatitis, we employed transgenic mice over-expressing PACAP in pancreatic β-cells (PACAP-Tg). In comparison to wild-type mice, PACAP-Tg mice exhibited more severe pathophysiological signs of the cerulein-induced pancreatitis at 12 h, as evidenced by higher serum amylase and lipase levels accompanied by the exacerbation of pancreatic edema, necrosis, and inflammation. Cerulein treatment increased mRNA expression of several proinflammatory cytokines (TNFα, IL-1β, and IL-6) at 12 h with similar magnitude both in wild-type and PACAP-Tg mice. In addition, the mRNA and protein levels of regenerating gene III β (RegIIIβ), a key factor in the pancreatic response to acute pancreatitis, were up-regulated at 24 h in wild-type mice upon cerulein administration, whereas they were attenuated in PACAP-Tg mice. These data indicate that over-expressed PACAP in pancreas enhances the cerulein-induced inflammatory response of both acinar cells, leading to aggravated acute pancreatitis, which was accompanied by a down-regulation of RegIIIβ, an anti-inflammatory factor. Keywords:: pituitary adenylate cyclase-activating polypeptide (PACAP), cerulein, acute pancreatitis, regenerating gene III β (RegIIIβ)